PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI SELF EFFICACY SISWA - Sarinah Septiani (Mat-Edukasia, 2020)
The purpose of this study is to describe mathematical communication skills using discovery learning learning models better than conventional learning for students of class VIII SMP Negeri 13 Merangin 2019/2020 academic year. The research method used was an experiment. The sampling technique used is probability sampling. Data collection techniques through tests. Based on the prerequisite test results of data analysis, it is known that data with normal and non-homogeneous distribution for hypothesis 4 while for data that is normal and homogeneous distribution for hypothesis 2. The test results show that: for hypotheses 1, 3, 4 and 5 are mathematical communication abilities with discovery models learning in terms of moderate, low and overall self efficacy is better than conventional teaching. For hypothesis two, mathematical communication skills with discovery learning models in terms of high self efficacy is not better or the same as conventional learning.